"I keep hearing reports on the news that it's a real problem at the moment": Public health nurses' understandings of sexting practices among young people. (25th February 2019) - Bradbury‐Jones, Caroline; Bradshaw, Sally; Clark, Maria; Lewis, Alison
Abstract: Over the past decade, the potential harms regarding young people's use of technology have attracted mounting political, media and research attention worldwide. One practice engaged in by many young people is that of "sexting" and the sharing of partially, or complete nude images ("selfies"). Such images are not always retained within private spaces and are prone to be shared, with significant psychosocial consequences for young people involved. A significant risk is the hidden nature of some online interactions, with potential for grooming and child sexual exploitation. As key professionals working with young people, public health nurses have potential to educate and explore the risks with them. Yet to date, to our knowledge there has been no research in relation to public health nurses' understandings of the practices involved or their potential harms. A qualitative study was undertaken drawing theoretically on the common‐sense model (CSM) to frame the analysis. Eighteen semi‐structured interviews were conducted with public health nurses in a region of England in 2016. Data were analysed through thematic analysis, and mapped to the five domains of CSM. Public health nurses' understandings of young people's sexting practices were shaped largely by media reports, rather than scientific, disciplinary knowledge. Sexting did not resonate with many public health nurses' own experiences of being a young person and was therefore difficult to understand. All were able to express an opinion about the causes and consequences of sexting and we present these as a "perceived hierarchy of risk". All public health nurses acknowledged the importance of their role in dealing with harm reduction associated with sexting among young people, but they need education and support to do this effectively and confidently. Findings can be transferred carefully to many contexts and countries because sexting is a practice among young people that transcends geographical boundaries.